In-depth Examination of Physicochemical Parameters of Borehole Water Samples in Borokiri, Niger Delta - Tope, Ojo Odunayo; Adejimi, Adeoye James; Emeka, Okoli Austin; Josphe, Inyang Namdie (Universitas Negeri Surabaya, 2024)
This research provides an in-depth examination of the physicochemical parameters of borehole water samples in Borokiri Port Harcourt, with an emphasis on temperature, pH, conductivity, total dissolved solids (TDS), and heavy metal concentrations (lead, copper, zinc, and manganese). This research objective is to undertake a complete hydrogeochemical evaluation of groundwater quality in Borokiri, with an emphasis on determining the levels of various physicochemical parameters and heavy metal pollutants. The study included comprehensive field surveys, collecting primary data at borehole locations. Samples were gathered during the rainy season, analyzed in Borokiri's laboratory for physicochemical and microbial parameters using established international methods. Data analysis employed various geochemical techniques, ensuring a thorough assessment of groundwater characteristics and quality. The mean temperature, roughly 29.97°C, is surrounded by a tight clustering, with a modest temperature range of 6.30°C. The average pH of 8.04 shows excellent constancy, as seen by a low standard deviation and a limited range. Conductivity has a mean of 417.00 S/cm, showing significant dispersion with a wider range. The mean total dissolved solids of 199.00 mg/L demonstrate a wide range. Piper and Durov diagrams reveal ion dominance and interaction among samples, supporting judgements on water resource management. The calculated Water Quality Index (WQI) values represent the status of water quality, with most samples displaying